COMPARATIVE ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF THE REGIONAL REVENUE AND EXPENDITURE BUDGET (APBD): A CASE STUDY OF SOUTH TAPANULI REGENCY AND MANDAILING NATAL REGENCY FOR THE 2024 PERIOD - Syifa Soleha; Lisbetria Simamora; Klara Srikandi Laia; Iskandar Muda; Andy Mulia (JIAR : Journal Of International Accounting Research, 2025)
The Regional Revenue and Expenditure Budget (Anggaran Pendapatan dan Belanja Daerah/APBD) has the role of the main instrument in reflecting the financial management of a region. The purpose of this study is to identify, compare, and analyze how effective and efficient the use of the Regional Revenue and Expenditure Budget (APBD) 2024 period. The analysis used is a quantitative descriptive method, in the form of describing the two districts based on data showing numbers. Especially in the numerical data on the financial ratio of Regional Original Revenue (PAD) and Regional Expenditure of related districts. This study provides a statement based on evidence of data from related district budget realization reports, especially in the efficiency criteria section in Mandailing Natal Regency in 2024 with less efficient classification. The identification of regional revenues and regional expenditures is carried out to provide an overview of the causes and become an input for the governments of South Tapanuli Regency and Mandailing Natal Regency, especially in their efficiency level.